267 A Rare Case of Primary Uterine Mesonephric Adenocarcinoma. (11th January 2018) - Kim, Grace; Veran-Taguibao, Sonia; Taguibao, Roberto
Abstract: Mesonephric neoplasms arise most commonly in sites where vestigial mesonephric or Wolffian duct remnants reside, which include the lateral vagina, uterine cervix, parametrium, broad ligament, mesosalpinx, and ovarian hilum. Pure mesonephric adenocarcinomas of the uterine corpus are exceptionally rare, with only 13 previously reported cases in the literature to date. We report here a case of a 37-year-old multiparous female patient with history of multiple cesarean sections. She initially presented to an outside institution with a two-month history of diffuse abdominal pain and menorrhagia without improvement on Provera and Norco. An endometrial endometrioid adenocarcinoma, FIGO Grade 1, was diagnosed on biopsy. Subsequently, the patient underwent a hysterectomy and bilateral salpingo-oophorectomy at our institution. Gross examination confirmed a 4.5 x 3.8 x 2.8 cm firm, tan, polypoid mass in the anterior endometrium invading into the deep myometrium. On microscopic examination, an infiltrative neoplasm with back-to-back dilated and small glands, and highly atypical, yet monomorphic, nuclei was appreciated. On the periphery of the tumor were foci of bland glandular profiles with luminal eosinophilic colloid-like material consistent with mesonephric hyperplasia. Minimal superficial cervical involvement was seen. Immunohistochemical studies were positive for GATA-3 and CD10 (focal), and negative for estrogen and progesterone receptors, in support of a diagnosis of uterine mesonephric adenocarcinoma. A spectrum of architectural patterns (tubular, ductal, retiform, papillary) can be seen in mesonephric adenocarcinomas. Glandular architecture with innumerable, closely approximated small glands is most common and bears histologic resemblance to endometrioid adenocarcinoma. The presence of intraluminal eosinophilic material, adjacent mesonephric hyperplasia, and a distinct immunoprofile often assists in differentiating mesonephric adenocarcinomas from other epithelial tumors. Mesonephric adenocarcinoma, most frequently seen in the cervix, can rarely present as a primary malignancy of the uterine corpus and remains in the differential diagnosis of uterine glandular malignancies.